Dienogest as a Maintenance Treatment for Endometriosis Following Surgery: A Systematic Review and Meta-Analysis - Liu, Yijun; Gong, Han; Gou, Jinhai; Liu, Xinghui; Li, Zhengyu (Frontiers in Medicine, 2021)
This study aimed to comprehensively assess the value of Dienogest (DNG) as a maintenance treatment following conservative surgery for endometriosis in terms of the outcomes of disease and pregnancy. We searched for relevant studies and trials up to November 2020 from PubMed, Cochrane Library, Medline, and EMBASE databases as well as the Web of Science. Patients who received DNG maintenance treatment were compared to those who received other treatments (OT), including the levonorgestrel-releasing intrauterine system (LNG-IUS) and gonadotropin-releasing hormone analogues (GnRH-a), or non-treatment (NT). The primary outcomes were disease recurrence and pregnancy rates. Eleven studies were included in this meta-analysis. The pooled analysis indicated that DNG maintenance treatment was associated with a lower rate of disease recurrence. A significant difference was observed in DNG maintenance treatment compared with NT, but not with OT, in the pregnancy rates postoperatively. Moreover, DNG maintenance treatment was related to a significant increase in vaginal bleeding and weight gain. DNG can be recommended as a maintenance treatment for patients with endometriosis to decrease the rates of disease recurrence following conservative surgery. However, DNG maintenance treatment has no advantage in improving pregnancy rates compared to OT.